2008
DOI: 10.7547/0980414
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Open Technique for the Achilles Tenotomy in Correction of Idiopathic Clubfoot

Abstract: Achilles tenotomy is performed for the residual equinus deformity in the Ponseti method of clubfoot treatment. In the present article, we describe a mini-open Achilles tenotomy technique to prevent complications that could occur during tenotomy. This technique was performed on 15 patients (25 feet) during a 3-year period in our clinic on patients whose equinus deformities could not have been corrected by manipulations. Clear improvement (mean angle, 30 degrees ) was observed in equinus in our patients, and we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…We have not observed any defects in the healing of the Achilles tendon: the palpable rigid band of the tendon appeared already three weeks after tenotomy, suggesting its successful regeneration. Despite the knowledge of some rare complications [12], Achilles tenotomy should be taken as a more conservative method than trying to aggressively treat with casts [13]. We are convinced, therefore, that the complex treatment of this defect requires not only exact knowledge of the conservative approach but also the set of different surgical interventions, like dorsal and peritalar release, osteotomy of the hindfoot and forefoot as well as supramalleolar osteotomy, particularly in the treatment of neurogenic club feet, where the per cent of relapses is much higher.…”
Section: Discussionmentioning
confidence: 99%
“…We have not observed any defects in the healing of the Achilles tendon: the palpable rigid band of the tendon appeared already three weeks after tenotomy, suggesting its successful regeneration. Despite the knowledge of some rare complications [12], Achilles tenotomy should be taken as a more conservative method than trying to aggressively treat with casts [13]. We are convinced, therefore, that the complex treatment of this defect requires not only exact knowledge of the conservative approach but also the set of different surgical interventions, like dorsal and peritalar release, osteotomy of the hindfoot and forefoot as well as supramalleolar osteotomy, particularly in the treatment of neurogenic club feet, where the per cent of relapses is much higher.…”
Section: Discussionmentioning
confidence: 99%
“…Several modifications of this technique which includes use of modified surgical blade designs and even mini open methods have been reported in an attempt to decrease these complications. 16,17 Percutaneous tenotomy with a needle was described earlier in literature to correct trigger finger deformity. 17 Minkowitz B et al, first described the use of a large gauge hypodermic needle to section the tendo Achilles percutaneously as a modification of Ponseti method.…”
Section: Discussionmentioning
confidence: 99%
“…The only article exposing Achilles tenotomy to be performed openly is that in which Dogan et al [8] reported a series of 25 cases. In this study, the investigators reported no complications related to the mini-open technique and concluded that the direct visualisation of the tendon with the mini-open incision might reduce the risk of neurovascular injury, especially for surgeons who are not experienced.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the investigators reported no complications related to the mini-open technique and concluded that the direct visualisation of the tendon with the mini-open incision might reduce the risk of neurovascular injury, especially for surgeons who are not experienced. However, the evaluation criteria were limited only to the obtained radiographical correction and neurovascular injury, and any information about tendon healing or the clinical results were not given [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation